PENGARUH PENGETAHUAN PAJAK, PERSEPSI ATAS EFEKTIFITAS SISTEM PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PPh PASAL 21 DALAM MELAPOR SPT (Studi Pada Dosen ASN di Politeknik Negeri Semarang) - Maulina Nailissyifa; Suryadi Poerbo; Umar Farouk (JOBS (Jurnal Of Business Studies), 2019)
This study aimed to determine the influence of tax knowledge, perception of taxation system effectiveness and tax sanctions on ASN Lecturer taxpayer compliance of income tax art. 21 at Semarang State Polytechnic in reporting SPT. Data analysis that used were instrument test, classical assumption test, multiple linear regression analysis, and hypothesis test. The sample that used in this study were 80 respondents that choosen using incidental sampling method. Hypothesis test results indicate that tax knowledge and tax sanctions partially influencing the taxpayer compliance in reporting SPT. Meanwhile, the perception of taxation system effectiveness does not influence the taxpayer compliance in reporting SPT. Furthermore, tax knowledge, perception of taxation system effectiveness and tax sanctions simultaneously influencing the taxpayer compliance in reporting SPT. The results of the coefficient of determination indicate that tax knowledge, perception of taxation system effectiveness and tax sanctions influencing the taxpayer compliance in reporting SPT by 43.8%. While the remaining 56.2% of taxpayer compliance in reporting SPT is influenced by other factors which were not observed in this study.